Cerebrovascular manifestations in neurosarcoidosis: how common are they and does perivascular enhancement matter?. Issue 10 (October 2018) - Bathla, G.; Watal, P.; Gupta, S.; Soni, N.; Capizzano, A.A.; Derdeyn, C.P.; Moritani, T.
Abstract : Aim: To determine the occurrence of ischaemic and haemorrhagic events in patients with neurosarcoidosis at presentation and follow-up and to evaluate its association with perivascular enhancement. Materials and methods: The MRI findings in patients with neurosarcoidosis who presented to our institute from 2002–2017 were retrospectively reviewed, with emphasis on cerebrovascular events. A chi-squared test was used to evaluate the statistical association with presence of perivascular enhancement. Results: A total of 49 patients (32 females and 17 males) were analysed. Ischaemic events were noted in four patients at presentation while parenchymal haemorrhages occurred in three patients. The combined occurrence of cerebrovascular events (CVEs) at presentation was 14%. On follow-up, three additional patients developed ischaemic infarcts, of which, one patient had parenchymal haemorrhage at presentation. Additionally, one patient also developed new parenchymal haemorrhages. In total, 10 patients in current cohort developed CVEs, either at presentation or on follow-up. Perivascular enhancement was seen in 50% of patients with cerebrovascular events and 18% of patients with neurosarcoidosis, but no CVEs. This was statistically significant ( p <0.05). Conclusion: CVEs in patients with neurosarcoidosis are more common than previously reported and appear to be significantly related to the presence of perivascular enhancement on imaging. Highlights: The authors present a review of 49 NS patients with emphasis on the occurrence of CVE, which are likely more frequent than previously thought. CVE in NS are significantly associated with PVE on imaging, occurring either along the lenticuostriate perforators or paraventricular veins. These patients tend to have a more aggressive clinical course when compared to NS patients without CVE. Patients with predominantly venous involvement may have distinct imaging findings on MRI and conventional angiogram studies.